PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE ANDROID MEREK SMARTFREN (Studi Kasus pada Pusat Penjualan Handphone di Matahari Simpang Lima Semarang) - Jean Shiska Malaon Latuconsina, 12.05.51.0020; Widyasari, Suzy (Students' Journal of Economic and Management, 2016)
This study aimed to analyze the effect of product quality, price perceptions and attitudes of consumers toward purchasing decisions Smartfren android phone. The data used are primary data obtained directly from the original source in the form of a questionnaire. The sample in this study is that consumers buy mobile phones brand Android phone Smartfren at the Sales Center Matahari Simpang Lima Semarang as many as 100 people. The sampling technique is purposive sampling. The criteria for the samples used in this study is consumers who make purchases Smartfreen Android mobile phone sales in Central Sun Semarang Simpang Lima, and consumers who are at least 17 years old. Test equipment used in this study testing the validity using factor analysis, reliability testing using Cronbach Alpha and hypothesis testing using multiple linear regression. The results of the analysis can be concluded that: the quality of products had significant and positive effect on purchasing decisions Smartfren android phone. Perception price had significant and positive effect on purchasing decisions Smartfren android phone. Consumer attitudes had significant and positive effect on purchasing decisions Smartfren android phone. Keywords: product quality, price perception, consumer attitudes and purchasing decisions.